Sonaten fur Klavier zu Zwei Handen: Band I - HAYDN, Joseph (Edition Peters)
Di dalam buku ini berisi lagu: Eb major; e minor; Eb major; g minor; C major; c# minor; D major; Ab major; D major; G major; G major